“It’s My Fault”: Exploring Experiences and Mental Wellness Among Korean International Graduate Students - Koo, Katie; Kim, Young Won; Lee, Joonyoung; Nyunt, Gudrun (Journal of International Students, 2021)
Mental health issues are on the rise on college campuses for all students, including international students. This qualitative study explores the mental wellness of Korean international graduate students, a sub-group that has received limited attention. By interviewing 18 Korean international graduate students in the United States, we found that limited English proficiency shapes various aspects of Korean international graduate students’ well-being; self-imposed pressures negatively influence mental wellness; self-blaming and an inability to express one’s feelings lead to further deterioration; and students turn to physical and religious/spiritual activities to improve their mental wellness. Implications for research and practice are discussed.